2011
DOI: 10.1002/sia.3763
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of chemically modified baker's yeast cells studied by AFM

Abstract: Chemical pretreatment is widely used to facilitate transformation of living cells when foreign components are introduced into a cell through the cell wall. The influence of appropriate chemicals on the wall properties and mechanism of transformation is still a matter of intensive studies. Saccharomyces cerevisiae cells (also known as baker's yeast) were investigated by atomic force microscopy (AFM). The cell walls were modified by lithium acetate and dithiothreitol. The AFM imaging was performed in liquid wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…AFM is a useful technique to determine the mechanical properties of living cells such as cells stiffness defined by Young’s modulus measurements. AFM force spectroscopy mode has been applied to measure the Young’s modulus of the whole cell and to analyze the statistical distribution of cell elasticity. …”
Section: Resultsmentioning
confidence: 99%
“…AFM is a useful technique to determine the mechanical properties of living cells such as cells stiffness defined by Young’s modulus measurements. AFM force spectroscopy mode has been applied to measure the Young’s modulus of the whole cell and to analyze the statistical distribution of cell elasticity. …”
Section: Resultsmentioning
confidence: 99%
“…Cells can be fixed mechanically in porous membranes, e.g., in our group, the cells were trapped within the micrometer-diameter holes of polymeric membranes (Fig. 3) (33). Wang et al invented a vacuum-based cell-holding device (34).…”
Section: Influence Of Cell Preparation On Measurement Resultsmentioning
confidence: 96%
“…Like bacteria, yeast are highly adaptable to environmental changes, and force experiments have been used to characterize cellular responses to harmful extracellular stimuli or changes in membrane composition. AFM force experiments revealed that elasticity of the S. cerevisiae cell wall increases in response to ethanol stress or elevated osmotic pressure, while Pillet et al found that prolonged exposure to heat stress can promote the formation of a stiff circular structure on the cell surface that is enriched in chitin. ,, Furthermore, modifications to the cell wall with chemicals or synthetic polymers that alter cell wall stiffness or thickness can be assessed directly using AFM. ,, As with bacteria, antifungal agents that target the yeast cell wall can dramatically alter the cell wall elasticity. The cell walls of S. cerevisiae and Candida albicans ( C. albicans ) both increased in stiffness after treatment with the antifungal caspofungin, though the effect was more pronounced in C. albicans .…”
Section: Force Experiments On Microbesmentioning
confidence: 99%